Synergistic effect of cold atmospheric pressure plasma and free or liposomal doxorubicin on melanoma cells - Konstantina Pefani-Antimisiari (Nature Portfolio, 2021)
Abstract The aim of the present study was to investigate combined effects of cold atmospheric plasma (CAP) and the chemotherapeutic drug doxorubicin (DOX) on murine and human melanoma cells, and normal cells. In addition to free drug, the combination of CAP with a liposomal drug (DOX-LIP) was also studied for the first time. Thiazolyl blue tetrazolium bromide (MTT) and Trypan Blue exclusion assays were used to evaluate cell viability; the mechanism of cell death was evaluated by flow cytometry. Combined treatment effects on the clonogenic capability of melanoma cells, was also tested with soft agar colony formation assay. Furthermore the effect of CAP on the cellular uptake of DOX or DOX-LIP was examined. Results showed a strong synergistic effect of CAP and DOX or DOX-LIP on selectively decreasing cell viability of melanoma cells. CAP accelerated the apoptotic effect of DOX (or DOX-LIP) and dramatically reduced the aggressiveness of melanoma cells, as the combination treatment significantly decreased their anchorage independent growth. Moreover, CAP did not result in increased cellular uptake of DOX under the present experimental conditions. In conclusion, CAP facilitates DOX cytotoxic effects on melanoma cells, and affects their metastatic potential by reducing their clonogenicity, as shown for the first time.